Cutting characteristics of electroplated diamond tools with laser-generated positive clearance. Issue 1 (2015) - Warhanek, M.; Walter, C.; Huber, S.; Hänni, F.; Wegener, K.
Abstract Conventional grinding wheels and dressing tools suffer from problematic chipping conditions at the abrasive grains, caused by near-zero or negative clearance angles at the micro-cutting edges. This paper introduces electroplated diamond dressing tools with positive clearance angles, generated by ultrashort pulsed laser ablation. A series of generic dressing experiments with varying parameters on vitrified bond corundum grinding wheels and long-term tests are presented for a comparative performance assessment of laser-conditioned and conventionally prepared tools. The results are applied to an analysis of the interdependency between the topography of the abrasive layer and the cutting characteristics of dressing tools.